Coordination of Communication Crisis Model - Faustyna Faustyna (Indonesian Journal of Education, Social Sciences and Research (IJESSR), 2020)
Purpose: This study aims to provide an ideal crisis communication coordination model in Medan Tourism Office in order to be able to respond to negative news that can enhance the reputation of culinary tourism areas in Merdeka Walk MedanMethodology: This study uses a constructivism paradigm, a study that provides constructive suggestions to the Medan Tourism Office to coordinate crisis communication. Finding: The results of the study found that the tourism office had not been the coordinator to implement crisis communication coordination because the Mayor of Medan had not yet issued a policy and coordination task for the communication crisis so that negative online media coverage could not be responded effectively. Significant: An effective and efficient crisis communication coordination model as an ideal suggestion to be applied by the Department of Tourism, so that negative media coverage online can be responded